Promoting Higher Order Thinking Skills in Literature Class via Critical Thinking Module (CTM) - Norhezan Che Teh; Nor Hashimah Isa; Ainon Omar (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2018)
Advancement in the innovation world, robotics and artificial intelligence as well as heavily globally-connected world among others has led to the impetus of Industrial Revolution (IR 4.0). Hence, work opportunities that exist today might not be available in the future as there is a huge possibility that they might be taken over by machines. This could result in job scarcity. Therefore, the challenge now is to prepare our students with the necessary skills to stay relevant and needed in the job market of the future. The ability to think on the higher level is amplified with IR 4.0. So, it is only wise to teach, train and prepare the students with this skill now. This paper shares the findings of a larger study on how the Critical Thinking Module (CTM) is able to assist higher order thinking (HOTs) among the students in Literature Classes. This research employs case study method and the subjects were selected using purposive sampling. The CTM focuses on the students’ ability to analyse, synthesise and evaluate. The activities included in CTM are everyday activities that will be able to be carried out in an hour and ten minutes period. All of the activities are student-centered and highlight on the importance of group work whereby discussion, collaboration and cooperation are vital. Data were gathered through test scripts and class observation. The participants were 9 students from a cluster school in Ipoh. They were observed for 18 weeks and the result of the study revealed that the students were better at HOTs verbally compared to written. The case study suggests the CTM is capable of aiding the students to think on the higher level.